2023
DOI: 10.3389/fmed.2023.1258037
|View full text |Cite
|
Sign up to set email alerts
|

Association between geriatric nutritional risk index and 28 days mortality in elderly patients with sepsis: a retrospective cohort study

Ling Li,
Xiuhong Lu,
Shuangwen Qin
et al.

Abstract: BackgroundThere is a significant controversy surrounding the impact of the geriatric nutritional risk index (GNRI) on mortality among elderly septic patients. This retrospective cohort study aimed to investigate the association between GNRI at admission and 28 days mortality in elderly septic patients.MethodsWe retrospectively analyzed data collected from the MIMIC IV database between 2009 and 2019, which included 2,834 septic patients aged 65 years and above. The exposure variable was the GNRI, determined acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…However, both the GNRI and PNI scores were reported as independent risk factors for short-term mortality in earlier studies. [ 24 , 33 ] In our study, HALP score showed no significant relationship with ICU mortality ( P = .78), which is inconsistent with earlier studies reporting that HALP is good at predicting mortality with either high or low sensitivity and specificity in geriatric patients with acute ischemic stroke. [ 29 , 34 ]…”
Section: Discussioncontrasting
confidence: 99%
“…However, both the GNRI and PNI scores were reported as independent risk factors for short-term mortality in earlier studies. [ 24 , 33 ] In our study, HALP score showed no significant relationship with ICU mortality ( P = .78), which is inconsistent with earlier studies reporting that HALP is good at predicting mortality with either high or low sensitivity and specificity in geriatric patients with acute ischemic stroke. [ 29 , 34 ]…”
Section: Discussioncontrasting
confidence: 99%